ANALISIS PENGARUH BORE UP TERHADAP PERFORMA MESIN SEPEDA MOTOR 4 LANGKAH YANG MENGUNAKAN BAHAN BAKAR PREMIUM DAN PERTAMAX - Gideon Perdana Marbun (2020)
Nowadays, the technology is growing rapidly, spur people to make innovations in automotive field that is growing widely, especially for motorcycles. The combustion engine is one of the internal combustion engines or which is often called an internal combustion engine, which is a combustion engine that converts electric heat into mechanical energy, the energy itself that widely used public facilities today are motorcycles. Bore up is an increase in piston size and Larger size or as desired. Research with the title of "Bore Up effect analysis on the performance of 4-step motorcycle engines using Premium and Pertamax fuel". The research aims to provide a real picture to the public that vehicles that have excessive compression must use fuel that has the appropriate octane. The goal is to find out how much the power, torque, and fuel consumption differences exist on standard cylinder blocks as well as premium and first-fuel modified cylinder blocks. Based on the analysis of the data done, the conclusion that from the comparison or difference of power, torque and fuel consumption that was exploited from the modified cylinder block result Mangakibatkan the compression is increasingly higher and is fitted with high fuel or octane use.